2012
DOI: 10.1007/s00216-012-6386-8
|View full text |Cite
|
Sign up to set email alerts
|

Degradation and epimerization of ergot alkaloids after baking and in vitro digestion

Abstract: The degradation and epimerization of ergot alkaloids (EAs) in rye flour were investigated after baking cookies and subsequently subjecting them to an in vitro digestion model. Different steps of digestion were analyzed using salivary, gastric, and duodenal juices. The degradation and bidirectional conversion of the toxicologically relevant (R)-epimers and the biologically inactive (S)-epimers for seven pairs of EAs were determined by a HPLC method coupled with fluorescence detection. Baking cookies resulted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 27 publications
4
24
0
Order By: Relevance
“…A shift in the epimeric ratio towards the -inine forms during baking has been elsewhere reported in the literature (Baumann et al, 1985;Wolff et al, 1988;Franzmann et al, 2010;Merkel et al, 2012). When looking separately to unprocessed and processed foods, some differences were observed.…”
Section: Occurrence Data On Foodsupporting
confidence: 60%
“…A shift in the epimeric ratio towards the -inine forms during baking has been elsewhere reported in the literature (Baumann et al, 1985;Wolff et al, 1988;Franzmann et al, 2010;Merkel et al, 2012). When looking separately to unprocessed and processed foods, some differences were observed.…”
Section: Occurrence Data On Foodsupporting
confidence: 60%
“…The action of the digestive juices to the alkaloid-CYN degradation is unclear. Merkel et al (2012), using a similar in vitro digestion model, also found degradation (at a moderate extent) of some ergot alkaloids by digestive juices, which was simply attributed to the presence of the digestive enzymes and varying pH conditions. On the other hand, it has been recently shown that some plant alkaloids can bind to bovine a-chymotrypsin (Zsila, K am an, Bog anyi, & J ozsvai, 2011) and fungal a-amylase (Tintu, Dileep, Augustine, & Sadasivan, 2012).…”
Section: Bioaccessibility Of Cynmentioning
confidence: 85%
“…Citrinin (CIT) could also be efficiently degraded by heating (Trivede et al 1992 ). EAs are partly degraded and epimerized during bread baking; the ratio between epimers shifts towards the -inine forms (EFSA 2012 ; Merkel et al 2012 ).…”
Section: Physical Processing Methodsmentioning
confidence: 99%